2020
DOI: 10.1097/wnr.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training and moderate-intensity continuous training alleviate β-amyloid deposition by inhibiting NLRP3 inflammasome activation in APPswe/PS1dE9 mice

Abstract: Recent study has demonstrated that high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) have the same effect to alleviate β-amyloid pathology in the hippocampus of APPswe/PS1dE9 (APP/PS1) mice. Activation of nucleotide binding and oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is pivotal and has been demonstrated to accelerate β-amyloid accumulation. The present study aimed to examine whether the exercise-induced β-amyloid reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Data from the literature indicate a positive role of physical exercise in the suppression of NLRP3. Studies on animal models indicate that physical activity prevents Aβ-induced disturbances in the NLRP3 inflammasome pathway in the hippocampus of mice as well as reduces β-amyloid deposition by regulating NLRP3 inflammasome-controlled microglial phagocytosis [ 161 , 162 ]. In addition, a low-calorie diet may also upregulate pathways that inhibit NLRP3 activation [ 163 ].…”
Section: Inflammasomes As a Possible Link Between Inflammation-associated Peripheral And Brain Insulin Resistance In Metabolic Disease Anmentioning
confidence: 99%
“…Data from the literature indicate a positive role of physical exercise in the suppression of NLRP3. Studies on animal models indicate that physical activity prevents Aβ-induced disturbances in the NLRP3 inflammasome pathway in the hippocampus of mice as well as reduces β-amyloid deposition by regulating NLRP3 inflammasome-controlled microglial phagocytosis [ 161 , 162 ]. In addition, a low-calorie diet may also upregulate pathways that inhibit NLRP3 activation [ 163 ].…”
Section: Inflammasomes As a Possible Link Between Inflammation-associated Peripheral And Brain Insulin Resistance In Metabolic Disease Anmentioning
confidence: 99%
“…Consistent with this notion, individualized exercise prescription has been reported to attenuate ASC gene expression in peripheral blood cells in obese individuals [ 38 ]. Animal studies have also shown that exercise suppresses NLRP3 inflammasome signaling in the aorta of obese mice [ 39 ], diabetic cardiomyopathy [ 40 , 41 ], and various brain regions, including the hippocampus [ 42 ], thus exerting protective effects against disease progression. However, the impact of exercise on adipose tissue NLRP3 inflammasome, as well as underlying mechanisms, remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that Aβ-induced pro-inflammatory factors such as IL-6 and TNF-α were possibly medicated by thioredoxin-interacting protein (TXNIP)/thioredoxin (TRX)/NOD-like receptor pyrin domain-containing protein 3 (NLRP3) pathway in microglial cells ( Feng and Zhang, 2019 ; Figure 2 ). Moreover, Aβ could induce the activation of NLRP3 inflammasome in microglia, contributing to the activation of microglia toward M1 polarization ( Halle et al, 2008 ; Liang et al, 2020 ; Zhang et al, 2020 ). Another study showed that Aβ led to the enhancement of pro-inflammatory cytokines such as IL-1β and IL-6 via regulating the homeostasis of ornithine decarboxylase and antizyme ( Cheng et al, 2019 ).…”
Section: The Role Of Microglia Polarization In the Pathogenesis Of Alzheimer’s Diseasementioning
confidence: 99%